Insights Into the Role of Epigenetic Factors Determining the Estrogen Response in Estrogen-Positive Ovarian Cancer and Prospects of Combining Epi-Drugs With Endocrine Therapy - Sarwar, Sadia; Alamro, Abir; Huq, Fazlul; Alghamdi, Amani (Frontiers in Genetics, 2022)
Ovarian cancer is one of the most lethal malignancies responsible for thousands of the death annually. Population at risk is continually on the rise due to acquired drug resistance, high relapse rate after surgery, incomplete knowledge on the etiology, cross-talk with other gynecological malignancies and diagnosis at an advanced stage when the disease is likely to have spread beyond the ovaries. Most ovarian tumors are thought to arise in surface epithelium somehow in response to changes in hormonal environment. Prolonged treatment with hormone replacement therapy (HRT) is also considered to be a contributing factor. Estrogens are found to influence etiology and progression of endocrine/hormone responsive cancers in a patient specific manner. The concept of hormonal manipulations got attention during last half of twentieth century when tamoxifen was approved by FDA as the first selective estrogen receptor modulator (SERM). Endocrine therapy (particularly antiestrogenic), that is found to be effective against breast cancer, can be a potential option for ovarian cancer as well. As it is now believed that global changes in epigenetics is also the hallmark of any tumor, increasing evidences show the involvement of epigenetic factors and chromatin alterations in the development of resistance to hormone therapy just like in case of chemotherapy resistance. A set of functionally related genes involved in epigenetic reprogramming are controlled by specific transcription factors (TFs). Thus, the activities of TFs mediate important mechanisms through which epigenetic enzymes and cofactors modify chromatin for worst outcome in a site-specific manner. Furthermore, the role of epigenetic aberrations involving histone modifications is established in ovarian cancer pathogenesis. The aim of this review is to provide insights on the role key epigenetic determinants of response as well as resistance to hormone therapy, current status of research along with its limitations and future prospects of epigenetic agents as biomarkers in early diagnosis, prognosis and personalized treatment strategies and directions with special emphasis on prospects of small phytoestrogenic molecules in combination with immunotherapy and epidrugs targeting ovarian cancer.